Falsafah Ekonomi Imam Al-Ghazali: Antara Sufisme dan Rasionalisme - Ayif fathurrahman (JES (Jurnal Ekonomi Syariah), 2023)
The article aims to understand the basis of Imam al-Ghazali’s economic thought. There are two streams studied, namely rationalism and sufism which are thought to influence Imam al-Ghazali’s economic thought. In this article, it is concluded that the philosophy of economic thought of Imam al-Ghazali knows no dichotomy between the world perspective and the hereafter ones. The point of view that was used did not stop at the worldview, but succeeded in containing Islamic values, which were oriented to the afterlife. In other words, Imam al-Ghazali’s economic thought is not only based on the aspect ratio, but is also controlled by ethics and moralilty. The ukhrawi's point of view that emphasized by Imam al-Ghazali serves as a lighter in economic activities based on ethics and morality. Because the nature of the economy is only one way to achieve a better life later in life. Imam al-Ghazali’s concept of the purpose of human life that focuses on the happiness of the hereafter, does not mean he rejects the happiness of the world. But according to him, the happiness of the world is majazi, while the happiness of the afterlife is intrinsic. In other words, Imam al-Ghazali succeeded in placing Islamic thought outside of Greek rationalist thought, but on the other hand, it also succeeded in melting mysticism in the sufi world.